New Bathynellidae (Crustacea) taxa and their relationships in the Fortescue catchment aquifers of the Pilbara region, Western Australia. Issue 2 (17th February 2019) - Perina, Giulia; Camacho, Ana I.; Huey, Joel; Horwitz, Pierre; Koenders, Annette
Abstract : In the past 20 years, the number of subterranean taxa discovered in Australia, especially in the Pilbara bioregion, has considerably increased due to incidental environmental surveys often associated with mining development. Bathynellidae are an important component of stygofauna and they occur in most Australian aquifers, but their collection and identification are difficult due to their habitat, and small and fragile bodies with conservative morphology. The study of Pilbaranella ethelensis in the upper Fortescue catchment contributed to a better understanding of the group at local scale, but knowledge at larger catchment scale is still limited. Abundant material collected by different environmental consultant companies on behalf of mining companies allowed an accurate analysis of the populations of Central Hamersley Range bathynellids. A new genus and one new species from the lower Fortescue catchment, Fortescuenella serenitatis gen. et sp. nov., is described using an approach that integrates morphological and molecular data. Three additional lineages are defined through morphology and DNA sequencing, using Automatic Barcode Gap Discovery and Poisson Tree Processes species delimitation methods. Based on previous knowledge on bathynellids and other stygofauna we expected to find multiple taxa, geographically restricted, possibly related to each other and to Pilbaranella genus described upstream of the Fortescue catchment. The phylogenetic reconstruction of the relationships among known lineages of the family in the Pilbara highlights a pattern of distribution characterized by a complex evolutionary history that does not reflect contemporary surface water catchments, suggesting a diversification that preceded the aridification processes started in the north of Western Australia during the Miocene. This study also clarifies the status of the 'cosmopolitan' Bathynella by excluding the Australian bathynellids from this genus. http://www.zoobank.org/urn:lsid:zoobank.org:act:E30796F4-1026-4278-BC13-45091DCB44CC